KINTAP RIVER WATER POLLUTION BY COAL MINING - Adyatma, Sidharta; Norfaida, Norfaida; Arisanty, Deasy; Alviawati, Eva; Hastuti, Karunia Puji (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Coal mining activities can cause environmental damage and high levels of water pollution. The research aims to determine the effect of coal mining on Kintap River water pollution in Tanah Laut Regency, South Kalimantan Province. The research sample was Kintap River water which was taken in 3 samples based on depth per point at four observation points (1 near the coal mine pond effluent, and 2, 3, 4 each 100 m downstream) and analyzed at the Banjarbaru Environmental Service laboratory based on five quality standard parameters for coal mining waste, namely pH, TSS, Fe, Mn, BOD and COD from the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 5 of 2022. Storet's calculation analysis is based on the Decree of the Minister of Environment No. 115 of 2003. The results show that the parameters that do not meet the quality standards are the pH and TSS parameters. The results of the Storet analysis obtained a value of -10 for the pH parameter and -8 for the TSS parameter, which means that pollution of the Kintap River water by coal mining is included in category B, which is lightly polluted.